Perancangan sistem informasi penyimpanan data koperasi berbasis web - Bryan Adha Elang Praditya; Yessica Nataliani; Penidas Fiodinggo Tanaem (AITI, 2021)
Cooperation as one of the driving wheels of the economy also require technology in the implementation of their operations. The application of the information system to the cooperation will affect the cooperative's performance. The Tani Makmur Cooperation in Klaten is a cooperative that helps farmers in managing rice fields, but does not yet have a web-based system that can integrate the required information. In this study, a web-based information system was designed that can be used as data storage, using a waterfall model. Data were collected by observation, interviews, and SWOT analysis. The resulting information system consists of the menu Master Data, Transactions, Reports, Settings, Graphics, Backups, and Help. Cooperation members can carry out storage, borrowing and installment transactions through the Transaction menu. The cooperation admin can view all transactions through the Reports menu. The resulting web-based information system can be used to store cooperation data, thereby expediting and accelerating the transaction process for Koperasi Tani Makmur customers and also reducing the risk of data loss..